Transversal Connections: The Cervantes Quatercentenary in Spain and its Comparison with “Shakespeare Lives” - Gregor, Keith (Multicultural Shakespeare: Translation, Appropriation and Performance, 2019)
Taking as its cue the 2016 quatercentenaries of the deaths of both Shakespeare and Cervantes, the essay offers some insights into the “transversal connections” between both events as celebrated in Spain and the UK. The questions it raises and attempts to resolve are fourfold: (1) What are the reasons and also the benefits of yoking together two such apparently disparate authors, whose strongest link is, arguably, the fact they both passed away in 1616? (2) What work is being done to restore these writers to life, especially in schools where, for a variety of reasons, literature has lost its core-curricular status, and in general society where the classics seem to have less and less import? (3) What might Shakespeare or Cervantes be said to stand for in their respective cultures, both in terms of the genres they wrote in (it is often forgotten, for instance, that Cervantes was also a poet and a dramatist) and the extra-literary values they are said to transmit? (4) What is the role of the State in the safeguarding and promotion of the nation’s cultural heritage?